FRI0061 Anakinra arrests joint destruction in patients with ra and established erosions. (1st June 2001) - Bresnihan, B; McCabe, D; Watt, I; Genant, H; Robbins, S; Newmark, RD
Abstract : Background: Patients with active RA and manifest erosive disease (at least 1 joint erosion) are likely to develop further joint damage. Objectives: The aim of this study was to evaluate the effect of anakinra on progressive joint damage in patients with erosive disease. Methods: Serial radiographs were obtained during a 24 week randomised placebo controlled study of 30 mg, 75 mg or 150 mg anakinra daily. Joint damage was quantified using both the Larsen and modified Sharp methods (Genant A&R, 41:1583, 98). Patients with at least 1 erosion at baseline were selected for study. Results: Approximately 75% of the 472 patients enrolled in the study had erosive disease (range 71–78% for each treatment group). The mean changes from baseline were highly significant for each anakinra dose group, when compared with placebo for reduction in the rate of joint destruction. The 75 and 150 mg dose groups arrested joint destruction (no radiographic progression) in a higher proportion of patients compared with placebo. A dose response was observed with regard to both the mean change from baseline of the modified Sharp scores and proportion of patients in whom joint destruction was arrested after 24 weeks of treatment. Conclusion: In patients with erosive disease, the rate of deterioration was significantly less in those who received anakinra. Significantly more patients with erosive RA who received anakinra for 24 weeks demonstrated an arrest of progressive joint damage. Moreover, an increasing benefit was associated with increasing dosages.